2005
DOI: 10.1002/atr.5670390107
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the bilateral micro-searching behavior for urban taxi services using the absorbing markov chain approach

Abstract: This paper develops a mathematical model that is based on the absorbing Markov chain approach to describe taxi movements, taking into account the stochastic searching processes of taxis in a network. The local searching behavior of taxis is specified by a logit form, and the O-D demand of passengers is estimated as a logit model with a choice of taxi meeting point. The relationship between customer and taxi waiting times is modeled by a double-ended queuing system. The problem is solved with a set of non-linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 11 publications
0
37
0
Order By: Relevance
“…In response to this lack, Wong, Wong, Bell, and Yang (2005) developed a mathematical model to consider the bilateralsearching behaviour of vacant taxi drivers and customers using the absorbing Markov chain approach. Yang et al (2010) developed another mathematical model to characterize the same bilateral-searching behaviour on road networks by incorporating a macroscopic searching-and-meeting model into the network model of Wong et al (2003).…”
Section: Introductionmentioning
confidence: 99%
“…In response to this lack, Wong, Wong, Bell, and Yang (2005) developed a mathematical model to consider the bilateralsearching behaviour of vacant taxi drivers and customers using the absorbing Markov chain approach. Yang et al (2010) developed another mathematical model to characterize the same bilateral-searching behaviour on road networks by incorporating a macroscopic searching-and-meeting model into the network model of Wong et al (2003).…”
Section: Introductionmentioning
confidence: 99%
“…Taxi customer bilateral searching and meeting behavior in a network was proposed in [15], which considered stochastic micro-searching behavior of both taxis and customers when they are searching for each other based on customer origin-destination (OD). The model featured location variation in the level of taxi services and stochastic microscopic searching behavior, such that the taxi searched for passenger locally in the network that incorporated Markov chain approach as a route for which transition probability or the link choice probability was specified by the customer pick-up rate within the network.…”
Section: Literature Reviewmentioning
confidence: 99%
“…By comparing the operation pattern of the Olympic period and pre-Olympic period, the authors showed the efficiency improvement in taxi operation during the Olympic period. Wong et al [22] developed a mathematical model based on the absorbing Markov chain approach to describe taxi movement, and they provided a novel and potentially useful measure of the urban taxi operation efficiency in a network. Recently, taxi service demand is analyzed by data mining and machine learning approaches.…”
Section: Related Workmentioning
confidence: 99%
“…This article aims to fill this gap by developing an approach to evaluating taxi driver performance comprehensively, and accurately rank taxi drivers by performance. Starting from previous studies [20][21][22], we take a step further to evaluate taxi driver performance by measuring taxi operation efficiency, which considers both the income generated by taxis in an occupied status and the cost when vacant.…”
Section: Introductionmentioning
confidence: 99%